1996
DOI: 10.1111/j.1365-3180.1996.tb01664.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth characteristics of spring barley and selected weeds. I. Effect of irradiance in growth chambers

Abstract: As fi part of a broader study, two experiments were carried out in growih chambers with three day/might temperature regimes (10'7, 20/14 and 30,'2rC) sttid>ing growth characteristics of individual seedlings over afour-week period. Experiment 1 was performed with spring barley {Hordeum vulgare L.), Gakopsis tetrahit L., and Viola Arvensis Murray. Experiment 2, with three irradiance levels at 20i'14°C, and one irradiance level at the other temperatures, was performed with spring harley, V. arvensis, Chenopodiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…SLA and LAR are also very plastic growth traits which are strongly affected by photon supply (Jeangros and Nösberger 1992). Decreasing irradiances cause the increase of SLA and LAR with the result that photon capture by the leaves is increased (Semb 1996). In present study, irradiance strongly affected photosynthetic and growth characteristics of M. chinensis and M. scabra, plants grown at lower irradiances had lower P max , SI, CI, and B and higher SLA and LAR.…”
Section: Plasticity Indices Of M Chinensis and M Scabramentioning
confidence: 44%
“…SLA and LAR are also very plastic growth traits which are strongly affected by photon supply (Jeangros and Nösberger 1992). Decreasing irradiances cause the increase of SLA and LAR with the result that photon capture by the leaves is increased (Semb 1996). In present study, irradiance strongly affected photosynthetic and growth characteristics of M. chinensis and M. scabra, plants grown at lower irradiances had lower P max , SI, CI, and B and higher SLA and LAR.…”
Section: Plasticity Indices Of M Chinensis and M Scabramentioning
confidence: 44%
“…These are very plastic growth traits and often strongly affected by irradiance (Jeangros and Nosberger 1992, Sakai 1995, Pothier and Prevost 2002. A decreasing irradiance causes an increase in LAR with the result that radiation captured by leaves increased (Semb 1996). Under a high irradiance, an increased LMA is associated with an adaptation to the high irradiance but it may be a result of adjustment to changes of temperature and humidity as well (Boardman 1977).…”
Section: Discussionmentioning
confidence: 99%
“…radiata grown under three treatments; LMR = leaf mass ratio; BMR = bulb mass ratio; RMR = root mass ratio. (Semb 1996). It is suggested that the high SLM corresponds with high proportions of support tissues and small cells (Castro-Díez et al 2000).…”
Section: Discussionmentioning
confidence: 99%